Characterization Of A Novel Hydrolytic Enzyme Producing Thermophilic Bacterium Isolated From The Hot Spring Of Azad Kashmir-Pakistan - Zahoor,Sana (2016)
ABSTRACT A thermophilic bacterium (TP-2) was isolated from the Tatta Pani hot spring in Azad Kashmir and was characterized using phenotypic and genotypic characters. The strain developed cream colored, round, smooth, flat and slimy colonies while the cells were Gram positive rods that ranged in size from about 2.1-3.6 μm to 0.2-0.3 μm in width. Sequence analysis of its 16S rRNA gene showed that isolate TP-2 had 89% homology with Geobacillus debilis. It grew within pH range of 5.5 to 8.5 with optimum growth at pH 7.0. The isolate showed optimum growth at 65ºC and gave positive results for gelatin hydrolysis (GEL), ortho nitrophenyl-β-D-galactopyranosidase (ONPG), and nitrate production and produced acid from sucrose, glucose and maltose. It utilized glucose, fructose, maltose, lactose, sucrose, xylan, starch, filter paper and carboxymethylcellulose as sole carbon source. Isolate TP-2 produced significant amount of industrially important enzymes i.e. extracellular α-amylase, CMCase, FPase, Xylanase, Protease and Lipase and intracellular CMCase and FPase.